Bagging, boosting and ensemble methods - Peter Bühlmann (Humboldt-Universität zu Berlin, Center for Applied Statistics and Economics (CASE), 2004)
Ensemble methods aim at improving the predictive performance of a given statistical learning or model fitting technique. The general principleof ensemble methods is to construct a linear combinationof some model fitting methods, instead of using a single fit of the method.
Keywords: 330